2017
DOI: 10.1021/acssuschemeng.7b01425
|View full text |Cite
|
Sign up to set email alerts
|

Soy Proteins As a Sustainable Solution to Strengthen Recycled Paper and Reduce Deposition of Hydrophobic Contaminants in Papermaking: A Bench and Pilot-Plant Study

Abstract: Hydrophobic contaminants (stickies) incorporated with recycled fibers cause severe papermaking processing and product quality problems, which lead to low runnability and increased production cost. Stickies negatively affect paper strength and many other properties. In this work, we propose a sustainable approach by the application of soy protein isolate (SPI), soy flour (SF), and soybean lipoxygenase (LOX) as agents to combat hydrophobic contaminants. Tests at the bench and pilot-plant scales and under conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…One explanation for the observed difference in the mechanical attributes between the two coatings can be in part due to the role of lignin in reducing the number of effective hydrogen bonds within the cellulosic network. Similar effect has been reported for the presence of wood extractives between the cellulosic fibers [36]. Yet, the obtained average tensile values are close to some commercially available cellulose-based films such as cellulose acetate (56 MPa) [37], and cellophane (40-90 MPa) [38,39], that have been used as barrier films in food-related applications [40].…”
Section: Film Propertiessupporting
confidence: 86%
“…One explanation for the observed difference in the mechanical attributes between the two coatings can be in part due to the role of lignin in reducing the number of effective hydrogen bonds within the cellulosic network. Similar effect has been reported for the presence of wood extractives between the cellulosic fibers [36]. Yet, the obtained average tensile values are close to some commercially available cellulose-based films such as cellulose acetate (56 MPa) [37], and cellophane (40-90 MPa) [38,39], that have been used as barrier films in food-related applications [40].…”
Section: Film Propertiessupporting
confidence: 86%
“…[ 3 , 5 , 6 , 21 , 30 ]. The hydrogen bonds between the hydroxyl groups prompt a highly ordered conformation of the cellulose chains in elementary fibrils that further facilitate adhesion with other polymeric components, e.g., with lignin or proteins, to form networks in aqueous media [ 12 , 31 ]. Since an energy-intensive mechanical grinding is required to separate the stacked fibrils, different types of pretreatments, such as alkaline [ 32 , 33 ], radiation [ 32 ], chemical [ 34 , 35 ], and enzymatic [ 36 , 37 ] are typically applied prior to the fibrillation process to remarkably lower the cost and energy.…”
Section: Chemistry Of Nanocellulose and Its Production Methodsmentioning
confidence: 99%
“…Cottonseed protein (CSP) have been used for the formulation of biobased products [18][19][20], as animal feed [21,22], in films, coatings and adhesives [19]. Several proteins have been previously reported as binders and strength agents in paper products, such as soy protein [23][24][25][26][27], gelatin, zein, and hydroxyproline-rich glycoprotein [28] and cottonseed protein [29]. Related work has shown that CSP isolate served as an effective strength agent for nonwovens [30].…”
Section: Introductionmentioning
confidence: 99%